Around The Farm (Chicago, IL P i kids and First Look and Find are trademarks of Phoenix International Publications, Inc, 2020)
Activities feature color identification, counting, matching, and more. Look and Find helps children develop skills while keeping them engaged as they explore exciting parts of the World of Eric Carle
Scientific Notions
Keywords: Colors; Counting